POLA KERJA SAMA SMK KOMPETENSI KEAHLIAN OTOMATISASI DAN TATA KELOLA PERKANTORAN DENGAN MITRA DUNIA KERJA DALAM IMPLEMENTASI KURIKULUM MERDEKA - Siti Umi Khayatun Mardiyah; Riana Muslikhah; Arwan Nur Ramadhan; Muhyadi Muhyadi; Santi Mustika Sari; Siti Ngainiyah; Ressa Nindi Puspita; Tutut Indra Kumala; Dwi Astuti (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This study examines the patterns of collaboration between Vocational High Schools (SMK) in the Office Automation and Management (OTKP) competency field and industry partners in the implementation of the Merdeka Belajar curriculum. A qualitative descriptive approach was employed, with data collected through in-depth interviews, direct observations, and documentation at five SMK Centers of Excellence in the Special Region of Yogyakarta and Central Java: SMKN 1 Depok Sleman, SMKN 1 Godean Sleman, SMKN 1 Wonosari, SMKN 2 Semarang, and SMK Muhammadiyah Muntilan Magelang. Informants were selected through purposive sampling, comprising vice principals for public relations and industry affairs, heads of OTKP competency programs, and OTKP teachers. Data were analyzed using the Miles and Huberman interactive model encompassing data collection, data reduction, data display, and conclusion drawing. Findings reveal that all schools formalized their partnerships through Memoranda of Understanding (MoU) valid for 3–5 years and initiated by the schools. Key collaboration activities include: student industrial internships (PKL/magang), guest practitioners teaching at schools, curriculum synchronization with industry inputs, industry-led recruitment of graduates, and job vacancy information dissemination through special employment exchanges (BKK). Challenges include difficulty finding competency-aligned industry partners, delays in job vacancy information, limited employer recognition of vocational competency certificates, negative impacts of the COVID-19 pandemic on students' work ethic and skills, mismatches between field tasks and OTKP competencies, and fluctuating partner capacity. Both schools and industry partners recommend a Quadruple Helix partnership model integrating government, industry, universities, and schools, alongside clearer teaching factory guidelines for the administrative field. Keywords: vocational education, school–industry partnership, Merdeka Belajar curriculum, OTKP, internship program, Quadruple Helix.